Disturbance Decoupling and Tracking Controller Design for Lateral Vehicle Dynamics - Mohammad Reza Satouri; Abolhassan Razminia; Saleh Mobayen; Pawel Skruch (IEEE Access, 2021)
This paper addresses an augmented nonlinear lateral vehicle and lane keeping dynamics in the presence of some unknown disturbances. In a geometric basin, considering unobservable spaces, their orthogonal complements, and using control invariant properties, a disturbance decoupling mechanism is designed for the mentioned dynamics. Afterward, a nonlinear tracking controller is designed to steer the vehicle on a reference path. The obtained disturbance decoupling and tracking controllers are implemented on a typical passenger car in a simulation environment to demonstrate the effectiveness and performance of the proposed method. It is shown that the controller decouples both the uniformly distributed and exponentially attenuated disturbances from the output.